Application of Gamification to Motivate Employees who Implement 5S in Automotive Sector Companies in Poland - Łukasz WACŁAWIK (Communications of International Proceedings, 2023)
The aim of the article is to present the application of the elements of gamification to motivate employees in the 5S implementation. 5S is one of the modern management methods that have been under crisis for the last few years. The crisis was caused mainly by the bureaucratization of the 5S audits, which effectively discouraged assembly line workers. It seems that the application of gamification together with the arrangement of competition and cooperation among employees may be a valuable solution thanks to which they will effectively implement the 5S method. With regard to the 5S method, the application of gamification consists in arranging competitions that resemble European Football Cup. Thus, there are eliminations, group stages, semifinals and finals. As there are defined targets of particular phases, the employees compete and cooperate ; the ones whose teams have the best results, are rewarded. Such activities reinforce companies internally by increasing their competitiveness or innovativeness and they strengthen the integration between the recipients and suppliers, which is necessary in Industry 4.0. The withdrawal from bureaucracy and the application of gamification seems to change the employees’ attitude to the 5S method. A rhetorical question remains how to maintain the staff motivation when the competition is over. An important objective of the article is to present the use of gamification outside its traditional areas of interest, i.e. marketing and human resources.
Keywords: Industry 4.0; gamification; 5S; motivation; crisis